Faulkner and Postmodernism - Abadie, Ann J.; Duvall, John N. (John Noel), 1956- (Book collections on Project MUSE., 2002)
Since the 1960s, William Faulkner, Mississippi's most famous author, has been recognized as a central figure of international modernism. But might Faulkner's fiction be understood in relation to Thomas Pynchon's Gravity's Rainbow as well as James Joyce's Ulysses? In eleven essays from the 1999 Faulkner and Yoknapatawpha Conference, held at the University of Mississippi, Faulkner and Postmodernism examines William Faulkner and his fiction in light of postmodern literature, culture, and theory. The volume explores the variety of ways Faulkner's art can be used to measure similarities and differe.